Multilevel diode clamped D-Statcom for power quality improvement in distribution systems - Jasti Venkata Ramesh Babu; Malligunta Kiran Kumar (Institute of Advanced Engineering and Science, 2021)
Power quality is one big issue in power system and a big challenge for power engineers today. Electrical consumers (or otherwise load devices) expect electrical power received power should be of first-class. Bad quality in electrical power directs to fuse blowing, machine overheating, increase in distribution losses, damage to sensitive load devices and many more. DSTATCOM is one of the FACTS controllers designed to improve the quality in electrical power and thus improving the performance of distribution system. This paper presents a multilevel DSTATCOM topology to enhance power quality in power distribution system delivering high-quality power to the customer load devices. Diode-clamped structure is employed for multi-level DSTATCOM structure. ‘PQ’ based control strategy generates reference signal which is further processed through level-shifted multi-carrier PWM strategy for the generation of gate pulses to multi-level DSTATCOM structure. Simulation work of proposed system is developed and the result analysis is presented using MATLAB/SIMULINK software. Performance of multi-level DSTATCOM topology is verified with fixed and variable loads.